Evaluation of the Effect of Herbicides and Growth and Development Regulators on the Biological and Economic Properties of Plants in Various Landscapes - Osipova, Rimma Hayk; Mkrtchyan, Anahit Tornik; Ghukasyan, Abraham Garnik; Harutyunyan, Slavik Samson; Larionov, Maxim Viktorovich; Sargsyan, Karine Shahen; Ghazaryan, Roland Hayk; Barbaryan, Ashxen Artavazd; Matevosyan, Lusine Gagik (Journal of Ecohumanism, 2024)
The research aimed to study the protective effect of the Epin-Extra and Zircon preparations when used with the Stomp and Dianat herbicides in plant cultivation. In all studies, barley served as a test culture. Barley is an excellent model bioobject for genetic and environmental studies. We studied the effect of these preparations on the initial stages of ontogenesis, growth, development, and productivity of barley. In order to determine the mutagenicity of herbicides, we used laboratory germination, growth dynamics, phytotoxicity, formation of chlorophyll mutations, cytotoxicity, and productivity of barley as tests. The following methods were used: (1) seed germination with the use of filter paper rolls and polyethylene, (2) cytogenetic analysis, and (3) field experiment. All studies were performed according to a single scheme. The experimental results were statistically processed. Studying the germination rate and laboratory germination of barley showed a positive effect of the Epin-Extra and Zircon growth regulators when combined with herbicides. Under the action of herbicides on 10-day-old barley seedlings, we observed a strong toxic effect, which was significantly reduced when herbicides acted jointly with growth regulators. The chlorophyll mutations found in the study of plant growth dynamics indicated a mutational process occurring under the action of the Dianat. The mutagenicity of the studied herbicides was revealed by the cytogenetic method. The drop in mitotic activity and an increase in the frequency of chromosome aberrations in meristematic cells of barley indicated this. The effect of the Epin-Extra and Zircon growth regulators improved the process of cell division and significantly reduced the frequency of chromosome aberrations; that is, at the cellular level, they were most effective. The protective effect of growth regulators, when used together with herbicides, was also manifested in a field experiment: Already when production doses of herbicides are reduced by half, the yield significantly increases, the effectiveness of bioprotection is maintained, and the use of plant growth regulators strengthens and enhances the result. Changing the recommended doses makes it possible to significantly reduce the pesticide pressure on agrocenoses, which can considerably improve the state of the environment. That is, practical tasks are also solved to obtain hygienically high-quality agricultural products and to ensure rational and environmentally safe farming. Based on our scientific and experimental material, it seems possible to promote the minimization and control of the applied chemicals in modern plant growing, taking into account the ecological and biological characteristics of the grown plants, the properties of ecosystems, the ecological-geographical and functional-economic characteristics of landscapes.